Saturnus månar : Månar och mindre himlakroppar - Arnadottir, Anna; Bloomer, Edward; Cronemyr, Emil; Bowers, Brad; Gustavsson, Martin (2019)
As we look up at night we see that our Earth has one moon orbiting it, the one we call the Moon. We have explored our moon with orbiters, rovers and astronauts, mapping it and studying its history. Other planets also have moons in orbit around them and these may look quite different from the Earth's moon. Some are small and look like asteroids, others are so icy they would become comets if they plunged on an elliptical orbit towards the inner solar system. This full dome planetarium production; "Saturnian Moons" is a part of a series titled "Moons Beyond Counting". In this installment we look closer at the Cassini space probe and learn about its mission to Saturn and its many moons.
Planetarium show series "Moons Beyond Counting" was produced in close collaboration with Royal Observatory Greenwich, London.
Keywords: Planetarium; Planeatiumvisning; Planetarium; Planetarium show